2001
DOI: 10.1046/j.1471-4159.2001.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotinic agonists stimulate acetylcholine release from mouse interpeduncular nucleus: a function mediated by a different nAChR than dopamine release from striatum

Abstract: Acetylcholine release stimulated by nicotinic agonists was measured as radioactivity released from perfused synaptosomes prepared from mouse interpeduncular nucleus (IPN) that had been loaded with [3 H]choline. Agonist-stimulated release was dependent upon external calcium and over 90% of released radioactivity was acetylcholine. The release process was characterized by dose response curves for 13 agonists and inhibition curves for six antagonists. a-Conotoxin MII did not inhibit this release, while a-conotoxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
88
0
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 148 publications
(93 citation statements)
references
References 38 publications
2
88
0
3
Order By: Relevance
“…All release experiments were conducted at room temperature using methods described previously (Grady et al, 1997(Grady et al, , 2001. In brief, after 3 H-neurotransmitter uptake was complete, aliquots of synaptosomes (80 l) were distributed onto filters and perfused with perfusion buffer [uptake buffer containing 0.1% bovine serum albumin, 1 M atropine, and either 10 M nomifensine for…”
Section: Methodsmentioning
confidence: 99%
“…All release experiments were conducted at room temperature using methods described previously (Grady et al, 1997(Grady et al, , 2001. In brief, after 3 H-neurotransmitter uptake was complete, aliquots of synaptosomes (80 l) were distributed onto filters and perfused with perfusion buffer [uptake buffer containing 0.1% bovine serum albumin, 1 M atropine, and either 10 M nomifensine for…”
Section: Methodsmentioning
confidence: 99%
“…Those receptors that are expressed on or near nerve terminals modulate calcium-dependent release of neurotransmitters [35,36,37,38] including dopamine [39,40,41,42], norepinephrine [43,44], glutamate [45,46], GABA [47], and acetylcholine [48,49]. Nicotinic agonist-stimulated release of dopamine has been studied extensively in the nucleus accumbens because these nAChRs may play a major role in regulating the reinforcing effects of nicotine [50,51,52].…”
mentioning
confidence: 99%
“…Nicotine influences DA transmission by activation of nicotinic acetylcholine receptors on DA neurons in the striatum [89][90][91][92][93] as well as on a variety of other neurotransmitter systems that are known to mediate nigrostriatal DA release, including glutamtergic, GABAergic, noradrenalinergic and cholinergic systems [52,53,[94][95][96][97][98]. In advanced PD patients, improvements in motor and cognitive symptoms were observed with administration of nicotine [55,56,99] however some studies showed no effect [100][101][102].…”
Section: Discussionmentioning
confidence: 99%